Análise da dinâmica sócio-espacial de uma área ribeirinha: um estudo das residências secundárias do rio Sucuriú em Três Lagoas, MS - Garcia, Rita Maria de Paula (2007)
The actions human beings imply momentary disposal in the territorial configuration and recondition the social relations, then, the space. The leisure and tourism are synonymous icons of the labor unfastening and of release, currently associates the valuation of the natural way and to the quality of life and well-being. As one of the consequences of this trend, the secondary residences disfigure and configure a new dimension and consumption of the landscape for the leisure and tourism, diversifies the local economy and reproduces the space in the confrontation of new territories. The artificial lake formed by the Hidreletric Plant "Engenheiro Souza Dias" in the city of Três Lagoas, Mato Grosso do Sul, is propitious scene for land divisions since the decade of 1970 in the area that understands the edges of the river Sucuriú. The objective of the research is to analyze the process of the territory production and consumption of the landscape for the leisure, for way of the introduction of secondary residences to the edges it river Sucuriú-MS. The research was delineated in bibliographical sources and registers, beyond empirical research. The secondary residences if present in opposition to the ways of public and remunerated lodging, with infrastructure characteristics of private leisure. The individuals go to the meeting of the antidaily one to usufruct of modest activities as culture and to enjoy of the company of familiar using next natural attributes to the permanent domicile allies to the financial availability.